Strategi Pengelolaan Website Melekhindu.com dalam Mengembangkan Literasi Keagamaan Hindu di Era Digital pada Acarya Media Nusantara - I Wayan Rahayu; Untung Suhardi; AA Ketut Patera (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of digital media has significantly transformed patterns of religious literacy, including within the context of Hinduism. Religious websites no longer function merely as information platforms but have become discursive spaces that shape religious understanding, attitudes, and character formation. This study aims to analyze the management strategies of the melekHindu.com website in developing Hindu religious literacy in the digital era. A qualitative descriptive approach was employed, with data collected through literature review, non-participant observation, and in-depth interviews with the website manager, editor, and contributors. Data were analyzed using Norman Fairclough’s critical discourse analysis to examine the relationship between text, discursive practices, and social context. The findings indicate that value-based content management, editorial curation, and community participation play a crucial role in strengthening religious moderation and Hindu character education. The study concludes that melekHindu.com functions as a reflective and transformative digital literacy medium that supports the development of moderate, ethical, and contextually grounded Hindu religious understanding.